ANALISIS YURIDIS TINDAK PIDANA PENGGUGURAN KANDUNGAN (STUDI PUTUSAN NOMOR 40/PID.B/2020/PN.WNO) - Timothy Pangihutan; Norbert Tanto Harjadi (Reformasi Hukum Trisakti, 2021)
The defendant Arvita Sari Winda Adi Prastowo Binti Suradi in November 2019, located in Pulegundes Hamlet, Sidoharjo Village, Tepus District, Gunung Kidul Regency or another place which is still within the jurisdiction of the Wonosari District Court, was legally and convincingly proven guilty of committing the crime of intentionally carrying out an abortion obstetrical is not in accordance with medical reasons by using curettage obtained through online media. Based on the analysis carried out, it can be concluded that the application and elements of the criminal act of abortion in the provisions of article 346 of the Criminal Code are not appropriate because based on the principle of lex specialis derogate legi generali, special rules apply that regulate types of sentencing.